(untitled) (REMUNOM, 2025)
International taxation plays a crucial role in the global economic landscape, especially in the context of increasing interdependence between countries. Double taxation, characterized by the imposition of similar taxes on the same income, assets, or transactions in different jurisdictions, represents a significant challenge for multinational companies and foreign investors. To mitigate this problem, international treaties to avoid double taxation (DTTs) emerge as essential instruments, establishing clear rules for the distribution of tax jurisdiction among signatory states. In Brazil, the main objectives of Double Taxation Treaties (DTTs) are to avoid double taxation, prevent tax evasion, and promote legal certainty, facilitating the flow of investments and international trade. However, the application of these treaties is not always peaceful, generating debates about their normative hierarchy, jurisprudential interpretation, and effectiveness in tax practice. Furthermore, Brazil’s resistance to adhering to certain international standards, such as those foreseen in the OECD Model, raises questions about the country’s attractiveness to foreign investors. Given this scenario, this work aims to analyze the main double taxation treaties signed by Brazil, their effects on the economy, and their legal implications. To this end, the guiding principles of International Tax Law, doctrinal and jurisprudential interpretations on the subject, as well as the challenges and perspectives for Brazil in the context of global taxation will be addressed.